REDUCING MATERNAL MORTALITY THROUGH COMMUNITY PARTICIPATION: THE GBANKO EXAMPLE - Galaa, S.; Umar, H.; Dandeebo, G. (UDS International Journal of Development, 2016)
Community Participation in health (CPIH) has been touted as the panacea to many health care delivery problems. For several decades, WHO and its allied agencies have churned out evidence of the efficacy of community participation in improving many health care outcomes across several countries. However, there is paucity of evidence with regards to its contribution in the reduction of maternal mortality in Sub-Saharan Africa.Â The paucity of information on the subject has necessitated the need for evidence-based research on the contribution of CPIH to maternal health outcomes within the context of MDG 5. This study examined the nature and level of Community Participation in maternal health issues in Gbanko, and the accompanying health outcomes using a qualitative case study approach. Data were collected from various key informants selected from a rural community setting and staff of the Ghana Health Service. Results indicate a high level of Community Participation in maternal and child health. Community Participation was in the form of active education campaigns, antenatal attendance, and skilled delivery at birth and post-natal attendance among others. These resulted in zero home delivery for the past 3 years, zero maternal deaths for 3 years in a row, over 90 % antenatal attendance, 100% skilled delivery at birth etc. Due to the impressive nature of the Gbanko maternal health situation, we recommend among other things that, communities should emulate this example. It is also recommended that every effort to sustain and build on the present gains should be made while eschewing complacency. Key Words: Community, Participation, Maternal Health, MDGs, Gbanko